Temporomandibular disorders in females: acupuncture compared to occlusal splint - Rezende, Maria Cristina Rosifini Alves [UNESP]; Sant´Anna, Crischina Branco Marques [UNESP]; Ávila de Aguiar, Sandra Maria Herondina Coelho [UNESP]; Bertoz, André Pinhiero de Magalhães [UNESP]; Hall, Kevin Bruce [UNESP]; Dyonisio, Ana Luiza Di Bella; Lima, Jacquelyne do Valle; Costa, Leonardo Portilha Gomes da; Alves-Rezende, Luís Guilherme Rosifini (My University, 2013)
To compare the effect of acupuncture and occlusal splint in the treatment of temporomandibular disorders (TMD) in female patients.Method: Forty-eight female patients (mean age of 39.3±6.8 years) with diagnosed pain in muscles or joint according to RDC/TMD criteria were attended at UNESP - Aracatuba Dental School. Including criteria were reported pain in the chewing muscles and/or in the temporomandibular joint measured by a visual analogue scale (range from 0 to 10) and a reported reduction of the maximum mouth opening. Excluding factors were major occlusal problems, systemic diseases, pregnancy and age below 18 years. After randomization, the first group was treated with acupuncture performed by instructed dentist. The second group was treated with occlusal splint. The outcome variables were assessed at baseline (prior to the first treatment session) and after 1, 3 and 6 months. Primary criteria of success were improvement of mouth opening and pain reduction.Result: Acupuncture group exhibited chewing pain decrease from 5 (at baseline) to 1, 2 and 1 after 1, 3 and 6 months, respectively. In the splint group, chewing pain decreased from 4 to 2, 1 and 2 after 1, 3 and 6 months, respectively. The mouth opening (in mm) increased from 28 (at baseline) to 42, 44 and 46 after 1, 3 and 6 months, respectively in the acupuncture group. In the splint group, mouth opening improved from 29 to 40 after 1 month, and to 43 and 42 after 3 and 6 months. A significant pain reduction was noted for both groups when compared to the baseline (p<.001; Wilcoxon test). Acupuncture group had a significant clinical improvement of opening mouth (Mann-Whitney). Conclusion: The present outcomes suggest a positive association among acupuncture and occlusal splint on the reduction of chewing pain. Acupuncture was more effective in the mouth opening increase.

Comparar el efecto de la acupuntura y la férula oclusal para el tratamiento de los trastornos temporomandibulares (TTM) en pacientes de sexo femenino.Método: Cuarenta y ocho pacientes de sexo femenino (edad media de 39,3 ± 6,8 años) con dolor diagnosticado en los músculos o articulaciones según RDC / fueron atendidos en la UNESP criterios TMD - Facultad de Odontología de Araçatuba. Incluyendo los criterios se informaron dolor en los músculos de la masticación y / o en la articulación temporomandibular medida mediante una escala analógica visual (rango de 0 a 10) y una reducción informado de la apertura máxima de la boca. Excluyendo factores fueron los principales problemas oclusales, enfermedades sistémicas, el embarazo y la edad menor de 18 años. Después de la aleatorización, el primer grupo fue tratado con acupuntura realizada por el dentista le indique. El segundo grupo fue tratado con férula oclusal. Las variables de resultado se evaluaron al inicio (antes de la primera sesión de tratamiento) y después de 1, 3 y 6 meses. Criterios primarios de éxito fueron la mejoría de la apertura oral y la reducción del dolor. Resultado: grupo de acupuntura mostró disminución del dolor de mascar a partir de 5 (en la línea base) a 1, 2 y 1 después de 1, 3 y 6 meses, respectivamente. En el grupo de férula, dolor de mascar se redujo de 4 a 2, 1 y 2 después de 1, 3 y 6 meses, respectivamente. La apertura de la boca (en mm) aumentó de 28 (en la línea base) a 42, 44 y 46 después de 1, 3 y 6 meses, respectivamente, en el grupo de acupuntura. En el grupo de férula, apertura de la boca mejoró 29 a 40 después de 1 mes, y para 43 y 42 después de 3 y 6 meses. Una reducción significativa del dolor se observó en ambos grupos en comparación con la línea de base (p <0,001, prueba de Wilcoxon). Acupuntura grupo tuvo una mejoría clínica significativa de la apertura de la boca (Mann-Whitney).Conclusión: Los presentes resultados sugieren una asociación positiva entre la acupuntura y la férula oclusal en la reducción del dolor de mascar. La acupuntura fue más eficaz en el aumento de la apertura bucal.

Comparar os efeitos da acupuntura e da placa oclusal no tratamento da DTM em mulheres. Método: 48 pacientes do gênero feminino (39,3 ± 6,8 anos), atendidas na Faculdade de Odontologia de Araçatuba/Unesp, com limitação de abertura bucal e dor orofacial diagnosticada com RDC e medida por escala analógica visual (0-10). Foram excluídas da amostra pacientes com problemas oclusais, doenças sistêmicas, gravidez e idade inferior a 18 anos. Após randomização, o primeiro grupo foi tratado com acupuntura (GI). O segundo, com placa oclusal (GII). As variáveis de desfecho foram avaliados no início (antes da primeira sessão de tratamento) e após 1, 3 e 6 meses. Principais critérios de sucesso foram ampliação da abertura bucal e redução da dor. Resultado: GI exibiu redução de dor ao mastigar de 5 para 1, 2 e 1 após 1, 3 e 6 meses, respectivamente. Em GII, dor ao mastigar diminui de 4 para 2, 1 e 2 após 1, 3 e 6 meses, respectivamente. A abertura bucal (mm) aumentou de 28 para 42, 44 e 46 após a 1, 3 e 6 meses,respectivamente, em GI. Em GII a abertura bucal melhorou de 29 para 40, após 1 mês, e 43 e 42 após 3 e 6 meses. Redução significativa da dor foi observada em ambos os grupos (p <0,001, teste de Wilcoxon). O grupo que recebeu acupuntura teve significativa melhora clínica de abertura bucal (Mann-Whitney). Conclusão: os resultados sugerem associação positiva entre placa oclusal e acupuntura na redução da dor orofacial. A acupuntura foi mais eficaz no aumento da abertura bucal.
Los trastornos temporomandibulares en las mujeres: la acupuntura comparada con placa oclusal
Desordens temporomandibulares em mulheres: acupuntura comparada ao tratamento com placa oclusal
Keywords: Dental occlusion; Pain; Masticatory muscles; Therapeutics; Oclusión dental; Dolor; Músculos masticadores; Terapéutica; Oclusão dentária; Dor; Músculos mastigatórios; Terapêutica